Current account imbalances: Possibilities for Trade Policy Action under the Auspices of the WTO – a German Perspective - Bastian Alm; Sebastian Weins (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2018)
Since 2011, Germany has consistently been the country posting the largest current account surpluses in the world. In recent years, this has led to a number of calls from economists and policy-makers in and outside Germany, and from international institutions and organisations, asking the Federal Government to take action to reduce the surplus. These calls have tended to focus on recommendations for action to strengthen private and public-sector investment and real wage growth in Germany. As current account imbalances have long become a global phenomenon, we would like to open a discussion on how this issue could be dealt with under multilateral trade policy.
Keywords: F13; F32; F40; 330; Current account balance; German current account surplus; Trade policy; WTO